Endostructural morphology in hominoid mandibular third premolars: Discrete traits at the enamel-dentine junction. Issue 136 (November 2019) - Davies, Thomas W.; Delezene, Lucas K.; Gunz, Philipp; Hublin, Jean-Jacques; Skinner, Matthew M.
Abstract: The mandibular third premolar (P3 ) exhibits substantial differences in size and shape among hominoid taxa, and displays a number of discrete traits that have proven to be useful in studies of hominin taxonomy and phylogeny. Discrete traits at the enamel-dentine junction (EDJ) can be accurately assessed on moderately worn specimens, and often appear sharper than at the outer-enamel surface (OES). Here we use microtomography to image the P3 EDJ of a broad sample of extant apes, extinct hominins and modern humans ( n  = 100). We present typologies for three important premolar discrete traits at the EDJ (transverse crest, marginal ridge and buccal grooves), and score trait frequencies within our sample. We find that the transverse crest is variable in extant apes, while the majority of hominins display a transverse crest which runs directly between the two major premolar cusps. Some Neanderthals display a unique form in which the transverse crest fails to reach the protoconid. We find that mesial marginal ridge discontinuity is common in Australopithecus anamensis and Australopithecus afarensis while continuous marginal ridges largely characterize Australopithecus africanus and Paranthropus . Interrupted mesial and distal marginal ridges are again seen in Homo sapiens and Neanderthals. Premolar buccal grooves, previously identified at the OES as important for hominin systematics, are again found to show a number of taxon-specific patterns at the EDJ, including a clear difference between Australopithecus and Paranthropus specimens. However, their appearance may be dependent on the morphology of other parts of the crown such as the protoconid crest, and the presence of accessory dentine horns. Finally, we discuss rare variations in the form of dentine horns that underlie premolar cusps, and their potential homology to similar morphologies in other tooth positions.